Novel Scheduling Algorithms for LTE Downlink Transmission - D. Talevski; L. Gavrilovska (Telfor Journal, 2012)
Long Term Evolution (LTE) is the new standard specified by 3GPP on the way towards the fourth generation mobile network. The LTE introduces enhanced data link mechanisms to support successful implementation of new data services across the network. The incorporated scheduling mechanisms can significantly contribute to this goal. In this paper novel scheduling algorithms are presented and compared to the Max C/I Downlink scheduler for LTE, which is characterized by high data rates at cell level, but poor fairness. The newly developed algorithms allow fair distribution of available resources. Simulation results presented in the paper show that the implementation of these newly developed algorithms enables improvement of the overall system capacity and user level performances.